Effect of Easy Axis Distribution on Exchange Bias Phenomenon in Read Element via the Granular Model - Daeng-am, Wassana; Chureemart, Phanwadee; Chureemart, Jessada (Science Essence Journal, 2018)
บทคัดย่อ แบบจำลองแกรนูลาร์ในระดับจุลภาคซึ่งมีพื้นฐานจากสมการพลศาสตร์การเคลื่อนที่ของแลนดอว์-ลิฟชิทซ์-กิลเบิร์ตถูกเสนอขึ้นเพื่อใช้สำหรับการศึกษาสมบัติแม่เหล็กพื้นฐาน เนื่องจากปรากฏการณ์ไบอัสแลกเปลี่ยนในระบบโครงสร้างวัสดุสองชั้นที่ประกอบด้วยวัสดุแม่เหล็กเฟอร์โรแมกเนติกและวัสดุแม่เหล็กแอนติเฟอร์โรแมกเนติก ซึ่งเป็นองค์ประกอบที่สำคัญของโครงสร้างหัวอ่านข้อมูลฮาร์ดดิสก์ไดร์ฟ แบบจำลองที่ถูกสร้างขึ้นนี้สามารถจำลองลักษณะโครงสร้างวัสดุที่มีความเสมือนจริงได้ โดยการรวมผลของการกระจายตัวของขนาดของเกรนภายในระบบรวมทั้งผลการกระจายตัวของทิศแกนง่ายภายในชั้นวัสดุแม่เหล็กแอนติเฟอร์โรแมกเนติกได้ นอกจากนี้ ยังสามารถรวมผลของการเกิดอันตรกิริยาระหว่างเกรนและอันตรกิริยาระหว่างชั้นวัสดุเพื่อให้การคำนวณมีค่าเสมือนจริงได้อีกด้วย จากการศึกษาพบว่าปัจจัยที่สำคัญได้แก่ ระยะเวลาที่ใช้ในการคำนวณวงปิดฮิสเทอรีซีส ขนาดของเกรนเฉลี่ย และปริมาณสนามแลกเปลี่ยนระหว่างชั้นวัสดุส่งผลกระทบอย่างมากต่อคุณสมบัติทางแม่เหล็กของโครงสร้างวัสดุแม่เหล็กสองชั้น โดยผลการคำนวณให้ผลที่สอดคล้องกับผลการทดลองได้เป็นอย่างดี นอกจากนี้ ยังพบว่าผลการกระจายตัวของทิศแกนง่ายส่งผลต่อการลดลงของสนามไบอัสแลกเปลี่ยนมากถึง 60% เมื่อมุมของการกระจายตัวมีค่าเท่ากับ 30 องศา สาเหตุเนื่องมาการกระจายตัวของทิศแกนง่ายของแมกนิไทเซชันในชั้นแม่เหล็กแอนติเฟอร์โรแมกเนติกส่งผลให้เกิดการลดลงของผลรวมสุทธิของปริมาณแมกนิไทเซชันในชั้นแอนติเฟอร์โรแมกเนติก จึงทำให้สามารถสรุปได้ว่าผลการกระจายตัวของทิศแกนง่ายเป็นอีกหนึ่งปัจจัยที่ส่งผลอย่างมากต่อการเกิดปรากฏการณ์ไบอัสแลกเปลี่ยนในหัวอ่านข้อมูลของฮาร์ดดิสก์ไดร์ฟ คำสำคัญ: สมการแลนดอว์–ลิฟต์ชิทส์–กิลเบิร์ต การกระจายตัวของทิศแกนง่าย สนามไบอัสแลกเปลี่ยน ABSTRACT The granular model at micromagnetic level based on Landau-Liftshitz-Gilbert (LLG) equation is proposed to investigate the fundamentally magnetic properties in exchange-biased bilayer system comprised of ferromagnetic (FM) and antiferromagnetic (AF) layers which are the main component of hard disk drive. The proposed model can be used to generate the realistic microstructure, including the distribution of grain size as well as the easy axis misorientation in AF layer. Moreover, the intragranular and interlayer exchange interactions are also included into the model for realistic calculation. The results showed that the vital factors such as the calculation time for hysteresis calculation, the magnetic grain size, and the exchange interlayer field significantly affected the exchange bias field, and all calculations gave good agreement with the other experimental works on exchange bias as well. In addtion, we found that the effect of easy axis misorientation gave rise to the reduction of exchange bias field over 60 percentages at the dispersion angle of 30 degrees. This is due to the fact that the dispersion of easy axis in AF layer causes the decrease of net AF magnetization used to pin the direction of FM layer. In conclusion, the easy axis misorientation in AF layer is the one of crucial factors affecting on the exchange bias phenomenon of read element in hard disk drive. Keywords: Landau – Liftshitz – Gilbert equation, easy axis misorientation, exchange bias field